2022
DOI: 10.30872/jinv.v18i1.10524
|View full text |Cite
|
Sign up to set email alerts
|

Peran rekruitmen, seleksi, dan penempatan: analisis kinerja karyawan

Abstract: AbstrakTujuan penelitian ini adalah untuk mengetahui dan menjelaskan seberapa besar pengaruh proses rekruitmen, seleksi, dan penempatan kerja terhadap kinerja karyawan PT. XYZ. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan metode angket atau kuesioner. Teknik pengambilan sampel dilakukan dengan purposive sampling dengan jumlah sample sebanyak 95 karyawan. Selanjutnya dilakukan uji hipotesis menggunakan model regresi linier berganda dengan uji t (parsial) dengan bantuan program SPSS. Hasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The role of recruitment, selection and performance of employees. Research by Shalahuddin et al (2022) "found that the results of Rekrutmen and selection have a positive influence on employee kine rj, and job placement also has a positive effect f on employee performance." Nasution ( 2019) "shows 33 partially, selection has a positive influence on employee performance."…”
Section: Introductionmentioning
confidence: 99%
“…The role of recruitment, selection and performance of employees. Research by Shalahuddin et al (2022) "found that the results of Rekrutmen and selection have a positive influence on employee kine rj, and job placement also has a positive effect f on employee performance." Nasution ( 2019) "shows 33 partially, selection has a positive influence on employee performance."…”
Section: Introductionmentioning
confidence: 99%